Weed diversity in the reclaimed lands in Middle Egypt - Mahmoud Saeed; Ashraf Soliman; Maged Ahmad; Shereen Korany; Emad Alsherif (Biodiversity Data Journal)
More land must be reclaimed for farming due to the expanding population and lack of arable land. Since weeds are considered to be one of the primary causes of agricultural obstacles, the current study sets out to ascertain the weed diversity of the recovered lands in Middle Egypt. We selected eight crop plants, five winter crops and two summer crops — along with five orchards to identify their weed diversity. We found 121 weed species from 91 genera across 26 families — 90 annuals, one biennial and 30 perennials — in the investigated crops and orchards. On the one hand, peach and pomegranate (pome) orchards had the fewest weed species (29 each), while wheat crops had the most (79 species). With six genera, Euphorbia was the largest genus and Poaceae had 29 species, the most abundant family. Therophytes were the most prevalent life form amongst weed species, accounting for an average of 72.5%, followed by phanerophytes (5.2%) and geophytes (7.5%). According to the Ward classification of crops and orchards, based on the weeds found there, the planting season had a major influence on the diversity of weeds, followed by the type of plant grown (crop or orchard). The findings demonstrated that the number of years of cultivation had an impact on the weed flora and soil properties in reclaimed fields. Additionally, the old reclaimed areas had higher soil salinity, which reduced the diversity of weeds. Furthermore, xerophytic weed species declined and hydrophytic weed species increased with longer reclamation periods. The current study aims to shed light on the diversity of weeds and their most common species in newly-reclaimed lands in Middle Egypt to facilitate a way to combat them.